A Toda Lattice in Dimension 2 and Nevanlinna Theory - Eremenko, A. (Журнал математичної фізики, аналізу, геометрії, 2007)
It is shown how to study the 2-D Toda system for SU(n+1) using Nevan- linna theory of meromorphic functions and holomorphic curves. The results generalize recent results of Jost-Wang and Chen-Li.Mathematics Subject Classification: 35Q58.